Modelagem matemática para estimativa da gordura corporal baseada em densitômetro radiológica - Beraldo, Lucas Menghin (2017)
The overfat is associated with many methabolic, psycological and structural diseases. The adolescence is indicated as the critical period for the development of habits associated with fat accumulation like physical inactivity, poor diet and sedentarism. Thus, this is a important moment to monitorig the population aiming the reduction of obesity and associated disease. The golden standard to evaluate the body fatness is the dual-energy x-ray absorptiometry. However, its laboratorial aspect prevents a wide use. This way, simpler techniques as the skinfold measurement should be model from more exact techniques for this monitoring. The existing models were developed with foreign populations that don't resemble the Curitiba Metropolitan Region habitants. This could lead to evaluation and diagnostic errors. Thus, the aim of this study is to product a model of body fatness analysis appropriate to children and adolescents from the Curitiba Metropolitan Region. Two sample were selected, the first one composed by 567 healthy adolescents aged between 10 and 18 years; the other one composed by 63 children with cerebral palsy between 3 and 10 years. The groups have both genders. The data of weight, height, age and skinfold thickness were collected, beyond the body composition evaluation by radiologic densitometry. The fatness percentage obtained by different skinfold and other anthopometric mesures equations among the adolescents was compared with the obtained by densitometry presenting associations below indicated (CCC<0,900). A tendency of underestimation by the skinfold equations was found, that resulted in higher specificity values and low sensitivity (being specificity the relative quantity of true negatives among those who do not have de clinical condition, and the sensitivity the relations of true positives amons those who have the considered condition). This indicates a major quantitaty of false negatives, that leads many overfat adolescents to be classify as eutrophic. The developed classificatory model for adolescents obtained an adjustment of R2 Negelkerke=0,829, sensitivity of 99,0% and specificity of 82,7% presenting diagnostic's indicators above that obtained by skinfold equations and BMI. For the children with cerebral palsy was developed a fat mass estimation model with adjustment of R2 =0,950 and standard error of estimative of 1,039. The equations used to convert the skinfold in body fatness measures were found to be inadequate for aplication in adolescents from Curitiba Metropolitan Region. The aplication of logistic and linear regression techniques have presented positive results, even from modeling in the children with cerebral palsy sample.